2015
DOI: 10.1159/000376576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO<sub>2</sub> Pneumoperitoneum on the Cognitive Function of Patients Undergoing Gynecologic Laparoscopy

Abstract: Aim: To evaluate the effects of CO2 pneumoperitoneum during gynecologic laparoscopy on patients' postoperative cognitive function. Methods: This prospective clinical study included 225 adult female patients with American Society of Anesthesiologists physical status I or II. Patients underwent conventional open surgery (group I, n = 115) or gynecologic laparoscopy using abdominal insufflation with CO2 to an intra-abdominal pressure of 15 mm Hg (group II, n = 110). Serum S100β and neuron-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…31 Furthermore, a prospective single-centre cohort study showed that internal jugular vein catheterisation in robot-assisted surgeries elevated intracerebral pressure. 32 Apart from the abovementioned, increased CO 2 crossing the blood-brain barrier can induce consecutive intra-operative hypercarbia and acidosis, leading to cerebral hypoxaemia, 33,34 which is associated with the release of vascular factors and actuate-venous short circuit opening, eventually resulting in cognitive impairment such as increased sleepiness, confusion, and loss of memory ( [35][36][37][38]. Although these studies provide some insight on the effects of CO 2 on brain functions, much work is still needed to clarify the cellular mechanism underlying the correlation between CO 2 absorption and cognition in the RALRP in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, a prospective single-centre cohort study showed that internal jugular vein catheterisation in robot-assisted surgeries elevated intracerebral pressure. 32 Apart from the abovementioned, increased CO 2 crossing the blood-brain barrier can induce consecutive intra-operative hypercarbia and acidosis, leading to cerebral hypoxaemia, 33,34 which is associated with the release of vascular factors and actuate-venous short circuit opening, eventually resulting in cognitive impairment such as increased sleepiness, confusion, and loss of memory ( [35][36][37][38]. Although these studies provide some insight on the effects of CO 2 on brain functions, much work is still needed to clarify the cellular mechanism underlying the correlation between CO 2 absorption and cognition in the RALRP in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercapnic acidosis causes vasodilation of cerebral vessels thereby increasing cerebral blood flow and intracranial pressure . In adults, hypercapnia decreases cerebral oxygen metabolism, alters cerebral neurotransmission, and increases markers of neuronal injury . Studies of permissive hypercapnia in ventilated premature and very low birth weight infants show progressively impaired cerebral blood flow autoregulation at PaCO 2 levels above 45 mmHg and an increasing risk of intraventricular hemorrhage with increasing PaCO 2 .…”
Section: Physiological Effects Of Hypercapniamentioning
confidence: 99%
“…33 In adults, hypercapnia decreases cerebral oxygen metabolism, alters cerebral neurotransmission, and increases markers of neuronal injury. [56][57][58] Studies of permissive hypercapnia in ventilated premature and very low birth weight infants show progressively impaired cerebral blood flow autoregulation at PaCO 2 levels above 45 mmHg and an increasing risk of intraventricular hemorrhage with increasing PaCO 2 . 67,68 Conversely, a more recent large randomized control trial using permissive hypercapnia in extremely low birth weight infants (PHELBI study) did not confirm an increased risk of intraventricular hemorrhage.…”
Section: Cerebrovascularmentioning
confidence: 99%
“…However, the procedure necessitates the creation of a pneumoperitoneum, which can adversely affect the patient’s respiratory, circulatory, and neurological systems. If not properly managed, it can lead to cognitive impairment [ 2 ]. Postoperative cognitive dysfunction (POCD), a condition that can manifest in the weeks following non-vascular surgery, has been reported in 10–54% of cases.…”
Section: Introductionmentioning
confidence: 99%